Agricultural Land Evaluation Using GIS-Based Matching Method in Highland Areas for Oil Palm Cultivation - Muhammad Rendana; Sahibin Abdul Rahim; Wan Mohd Razi Idris; Zulfahmi Ali Rahman; Tukimat Lihan (Universitas Sebelas Maret, 2022)
Oil palm (Elaeis guineensis) is one of the commodity crops and is mostly found in tropical lands. This study aimed to analyze the current and potential land suitability for oil palm using the geographic information system (GIS) technique. The study was conducted in the Ranau District, Sabah State, Malaysia. Field activity was carried out to collect soil samples and land information in the study area. Land suitability was then assessed using the matching method and GIS software was employed to produce a land suitability map for oil palm. The results indicated that the current land suitability classes in the study area were highly suitable (S1) with a total area of 99,118 ha (27.4%); moderately suitable (S2) with 110,108 ha (30.4%); marginally suitable (S3) with 109,533 ha (30.2%); currently not suitable (N1) with 2,728 ha (0.7%) and permanently not suitable (N2) with 40,693 ha (11.3%). Meanwhile, the potential land suitability classes showed 198,206 ha (54.7%) for S1; 123,281 ha (34%) for S2 and 40,693 ha (11.3%) for N2. Suitable areas that could be planted with oil palm included the gently sloping flank and the low gradient slope margin. Availability of nutrients and work capability were the dominant limiting factors in the study area. The outputs of this study recommend that the Ranau District has the potential for oil palm although it still needs land improvements for sustainable oil palm cultivation.